Towards the Use of Adsorption Methods for the Removal of Purines from Beer - Catarina Almeida; Márcia C. Neves; Mara G. Freire (Molecules, 2021)
Beer corresponds to a fermented alcoholic beverage composed of several components, including purine compounds. These molecules, when ingested by humans, can be catabolized into uric acid, contributing to uric acid’s level increase in serum, which may lead to hyperuricemia and gout. To assure a proper management of this disease, physicians recommend restrictive dietary measures, particularly by avoiding the consumption of beer. Therefore, it is of relevance to develop efficient methods to remove purine compounds from alcoholic beverages such as beer. In this review, we provide an introduction on fermented alcoholic beverages, with emphasis on beer, as well as its purine compounds and their role in uric acid metabolism in the human body in relation to hyperuricemia and gout development. The several reported enzymatic, biological and adsorption methods envisaging purine compounds’ removal are then reviewed. Some enzymatic and biological methods present drawbacks, which can be overcome by adsorption methods. Within adsorption methods, adsorbent materials, such as activated carbon or charcoal, have been reported and applied to beer or wort samples, showing an excellent capacity for adsorbing and removing purine compounds. Although the main topic of this review is on the removal of purine compounds from beer, other studies involving other matrices rather than beer or wort that are rich in purines are included, since they provide relevant clues on designing efficient removal processes. By ensuring the selective removal of purine compounds from this beverage, beer can be taken by hyperuricemic and gouty patients, avoiding restrictive dietary measures, while decreasing the related healthcare economic burden.